2022
DOI: 10.3390/biology11101506
|View full text |Cite
|
Sign up to set email alerts
|

Latitude-Induced and Behaviorally Thermoregulated Variations in Upper Thermal Tolerance of Two Anuran Species

Abstract: Although thermal tolerance along geographical gradients gives an insight into species’ response to climate change, current studies on thermal tolerance are strongly skewed towards global-scale patterns. As a result, intraspecific variations are often assumed to be constant, despite a lack of evidence. To understand population-specific responses to thermal stress, we investigated the presence of intraspecific variations in the critical thermal maximum (CTmax) of tadpoles in two anuran species, Rana uenoi and Bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 60 publications
0
2
0
Order By: Relevance
“…The ability, or not, to behaviorally thermoregulate has been shown to impact local adaptation (Huey et al, 2003). In a study on two frog species, one species that does not behaviorally thermoregulate had a latitudinal cline in CTmax, but this pattern was not detected in a second species that does behaviorally thermoregulate allowing it to buffer changes in temperature without adapting to local climates (Kim et al, 2022). Some known mechanisms for Aedes mosquitoes to behaviorally thermoregulate are altering wing beat frequency and only increasing activity during cooler parts of the day (Reinhold et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…The ability, or not, to behaviorally thermoregulate has been shown to impact local adaptation (Huey et al, 2003). In a study on two frog species, one species that does not behaviorally thermoregulate had a latitudinal cline in CTmax, but this pattern was not detected in a second species that does behaviorally thermoregulate allowing it to buffer changes in temperature without adapting to local climates (Kim et al, 2022). Some known mechanisms for Aedes mosquitoes to behaviorally thermoregulate are altering wing beat frequency and only increasing activity during cooler parts of the day (Reinhold et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Deutsch et al, 2008;Sentinella et al, 2020;. Global studies, however, have usually used only one population per species (Kim et al, 2022), neglecting that intraspecific variation exists at both sides of the WT equation Villeneuve et al, 2021). Also, recent studies have shown that species at the same latitude or elevation may have contrasting between WT and population dynamics, range limits, or extinction risk (Soroye et al, 2020).…”
Section: Running Title: Biases Of the Warming Tolerance Indexmentioning
confidence: 99%